Evaluation of Dietary Intake and Body Composition of Collegiate American Football Players - Güneşliol, Bartu Eren; Baş, Murat (Progress in Nutrition, 2022)
Aim: The data obtained from previous studies on dietary intake and body composition of American football players, which may pose a health risk, also raise concern for collegiate American football players, especially for linemen. Therefore, this study aimed to evaluate the dietary intake and body composition of collegiate American football players by position groups. Methods: One-hundred and eighty-five collegiate American football players voluntarily participated in this observational study. Body composition was evaluated by both anthropometric measurements and bioelectrical impedance analysis. 3-day diet records were taken to determine dietary intake. Results: Energy, carbohydrate and protein intakes of defensive linemen (DL) (27.84±12.85 kcal/kg/day, 2.73±1.35 g/kg/day, and 1.29±0.68 g/kg/day respectively) and offensive linemen (OL) (25.98±9.17 kcal/kg/day, 2.47±0.85 g/kg/day, and 1.21±0.61 g/kg/day, respectively) were significantly lower than receivers (R) (41.49±20.12 kcal/kg/day, 4.31±2.34 g/kg/day, and 1.81±0.91 g/kg/day respectively). Collegiate American football players consumed high amounts of fat, dietary cholesterol, and sodium but were low in carbohydrates and potassium. Average body mass index (BMI) and body fat percentage (BFP) values of DL (31.38±4.43 kg/m² and 26.13±8.79%, respectively) and OL (32.95±4.77 kg/m² and 30.06±7.33%, respectively) were significantly higher than other position groups. Conclusions: In this study, collegiate American football players followed an unbalanced diet in terms of many nutrients. Most DL and OL were obese. We concluded that it would be useful to provide nutritional education for collegiate American football players, and specific nutritional strategies should be developed to reduce the risk of obesity-related diseases in linemen.